2015
DOI: 10.4054/demres.2015.32.39
|View full text |Cite
|
Sign up to set email alerts
|

The reliability of in-home measures of height and weight in large cohort studies

Abstract: Background With the emergence of obesity as a global health issue an increasing number of major demographic surveys are collecting measured anthropometric data. Yet little is known about the characteristics and reliability of these data. Objectives We evaluate the accuracy and reliability of anthropometric data collected in the home during Wave IV of the National Longitudinal Study of Adolescent to Adult Health (Add Health), compare our estimates to national standard, clinic-based estimates from the National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Height and weight were measured in Waves II, III, and IV using a tape measure and a digital scale by trained nonmedical field interviewers; height was measured to the nearest 0.5 cm, and weight was measured to the nearest 0.1 kg . Information on BMI was obtained by calculating weight (kg) divided by squared height (m 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Height and weight were measured in Waves II, III, and IV using a tape measure and a digital scale by trained nonmedical field interviewers; height was measured to the nearest 0.5 cm, and weight was measured to the nearest 0.1 kg . Information on BMI was obtained by calculating weight (kg) divided by squared height (m 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Self‐reported health was assessed as: “In general, how is your health?” Frequency of cigarette smoking among the past 30 days and frequency of alcohol consumption in the past 12 months were asked. Body mass index (BMI) was calculated from standing height measured with a steel tape and weight measured with a high capacity digital bathroom scale . Normal weight status was defined as BMI <25.0 kg/m 2 and overweight as BMI between 25.0 and 29.9 kg/m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Body mass index (BMI) was calculated from standing height measured with a steel tape and weight measured with a high capacity digital bathroom scale. 18 Normal weight status was defined as BMI <25.0 kg/m 2 and overweight as BMI between 25.0 and 29.9 kg/m 2 . Class 1 obesity was defined as BMI between 30 and 34.9 kg/m 2 , class 2 obesity as BMI between 35.0 and 39.9 kg/m 2 , and class 3 obesity as BMI 40.0 kg/m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…These readings were used to estimate BMI in kg/m 2 . A quality control study where participants were tested and then retested 1 -2 weeks later, showed that the assessment methods used produced highly reliable height, weight, and BMI measures (intra-class correlation coefficients from 0.98 -1.00; Hussey et al, 2015).…”
Section: Methodsmentioning
confidence: 99%